Second special section on religion and territorial politics in southern Europe. Issue 1 (2nd January 2016) - Giorgi, Alberta; Itçaina, Xabier
ABSTRACT: The three articles included in this second special section devoted to the interactions between religion and territorial politics in southern Europe continue the underlying research questions about the multiscalar interactions between religious mobilisation and policymaking, focusing on different denominations and scales of observations. The three articles point out three relevant elements for the analysis of religion and local politics. First, they show how contextualised exogenous factors influence the structures of opportunities for religions in the public and the political spheres. Second, they inchoately reveal the weakness of simplistic readings of the secularisation thesis. Third, they evidence the importance of a local and localised approach in analysing the relationships between religion and politics.